2012
DOI: 10.1002/chem.201202614
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Asymmetric Hydrogenation of 3‐Oxoglutaric Acid Derivatives: A Study of Unconventional Solvent and Substituent Effects

Abstract: A series of 3-oxoglutaric acid derivatives have been hydrogenated in different solvents in the presence of [RuCl(benzene)(S)-SunPhos]Cl (SunPhos = (2,2,2',2'-tetramethyl-[4,4'-bibenzo[d][1,3]dioxole]-5,5'-diyl)bis(diphenylphosphine)). Unlike simple β-keto acid derivatives, these advanced analogues can be readily hydrogenated in uncommon solvents such as THF, CH(2)Cl(2), acetone, and dioxane with high enantioselectivities. Two possible catalytic cycles have been proposed to explain the different reactivities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…For most examples in Table , higher ee values were observed in THF than in EtOH. To further explore the solvent effects, some other uncommon solvents were also tested 59. Overall, acetone was found to be an even better solvent than THF, especially for 48e and 48j .…”
Section: Substrates With Multiple Carbonyl Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…For most examples in Table , higher ee values were observed in THF than in EtOH. To further explore the solvent effects, some other uncommon solvents were also tested 59. Overall, acetone was found to be an even better solvent than THF, especially for 48e and 48j .…”
Section: Substrates With Multiple Carbonyl Groupsmentioning
confidence: 99%
“…Studies on various substituted 3‐oxo‐glutaric acid derivatives revealed an incredible substitution and solvent effect (Scheme ) 59. Even with the same skeleton ( 48n – r ), different substituents had inexplicable influences on the reactivity and enantioselectivity.…”
Section: Substrates With Multiple Carbonyl Groupsmentioning
confidence: 99%
See 2 more Smart Citations